CONTROVERSIAL ISSUES OF RADIOLOGIC DIAGNOSIS OF ADENOMYOSIS IN REPRODUCTIVE LOSSES - Alexey V. Pomortsev; Yulia V. Grushevskaya; Tatyana B. Makukhina (Кубанский научный медицинский вестник, 2019)
Aim. The aim is to analyze the data thus far published on the radiologic diagnosis of adenomyosis in patients with reproductive problems in order to determine promising areas for further scientifi c research.Materials and methods. An information search for subsequent analysis was performed using E-Library, PubMed and CochraneLibrary electronic bibliographic databases with the following keywords: “ultrasound diagnosis of adenomyosis”, “MRI adenomyosis”, “junctional zone adenomyosis”, “ultrasound adenomyosis”, “diagnosis adenomyosis”, “magnetic resonance imaging adenomyosis”, “adenomyosis junction”.Results. Imaging techniques are prioritized in diagnosing the initial incidence of adenomyosis. The value of such techniques increases when analyzing the causes of implantation failures. Key issues associated with the modern radiologic diagnosis and monitoring of adenomyosis during treatment have been considered on the basis of the standardization of studies, classifi cation of the disease, assessment of the diagnostic accuracy and prognostic value of imaging techniques in patients with reproductive losses and infertility.Conclusion. Promising areas of scientifi c research are found to be the specifi cation of optimal diagnostic timeframes, informativity of diagnostic criteria for 3D reconstruction, MRI, elastography, angiography, as well as the development of prediction methods for healthy childbearing and monitoring the treatment effectiveness.